Pcgf1 Regulates Early Neural Tube Development Through Histone Methylation in Zebrafish - Li, Xinyue; Ji, Guangyu; Zhou, Juan; Du, Jingyi; Li, Xian; Shi, Wei; Hu, Yong; Zhou, Wenjuan; Hao, Aijun (Frontiers in Cell and Developmental Biology, 2021)
The neural induction constitutes the initial step in the generation of neural tube. Pcgf1, as one of six Pcgf paralogs, is a maternally expressed gene, but its role and mechanism in early neural induction during neural tube development have not yet been explored. In this study, we found that zebrafish embryos exhibited small head and reduced or even absence of telencephalon after inhibiting the expression of Pcgf1. Moreover, the neural induction process of zebrafish embryos was abnormally activated, and the subsequent NSCs self-renewal was inhibited after injecting the Pcgf1 MO. The results of in vitro also showed that knockdown of Pcgf1 increased the expression levels of the neural markers Pax6, Pou3f1 and Zfp521 at 24 h and 48 h, but decreased the pluripotency markers Oct4, Hes1 and Nanog, which further confirmed that Pcgf1 was indispensable for maintaining the pluripotency of P19 cells. To gain a better understanding of the role of Pcgf1 in early development, we analysed mRNA profiles from Pcgf1 deficient P19 cells using RNA-seq. We found that the differentially expressed genes were enriched in many functional categories which related to the development phenotype, and knockdown of Pcgf1 increased the expression of histone demethylases (Kdm5a, Kdm5d and Kdm7a). Finally, our results showed that Pcgf1 loss-of-function decreased the levels of H3K27me3 at the promoters of Ngn1 and Otx2, and the levels of H3K4me3 at the promoters of Pou5f3 and Nanog. Together, our findings reveal that Pcgf1 might function as both a facilitator for pluripotent maintenance and a repressor for neural differentiation.